Cathepsins B, D, and G Are Expressed in Metastatic Head and Neck Cutaneous Squamous Cell Carcinoma - Humphries, Felix; Chang-McDonald, Bridget; Patel, Josie; Bockett, Nicholas; Paterson, Erin; Davis, Paul F.; Tan, Swee T. (Frontiers in Oncology, 2021)
Aim: We have previously demonstrated the presence of two cancer stem cell (CSC) subpopulations within metastatic head and neck cutaneous squamous cell carcinoma (mHNcSCC) expressing components of the renin-angiotensin system (RAS), which promotes tumorigenesis. Cathepsins B, D and G are enzymes that constitute bypass loops for the RAS. This study investigated the expression and localization of cathepsins B, D, and G in relation to CSC subpopulations within mHNcSCC. Methods: Immunohistochemical staining was performed on mHNcSCC tissue samples from 20 patients to determine the expression and localization of cathepsins B, D, and G. Immunofluorescence staining was performed on two of these mHNcSCC tissue samples by co-staining of cathepsins B and D with OCT4 and SOX2, and cathepsin G with mast cell markers tryptase and chymase. Western blotting and quantitative reverse transcription (RT-qPCR) were performed on five mHNcSCC samples and to four mHNcSCC-derived primary cell lines, to determine protein and transcript expression of these three cathepsins, respectively. Enzyme activity assays were performed on mHNcSCC tissue samples to determine whether these cathepsins were active. Results: Immunohistochemical staining demonstrated the presence of cathepsins B, D and G in in all 20 mHNcSCC tissue samples. Immunofluorescence staining showed that cathepsins B and D were localized to the CSCs both within the tumor nests (TNs) and peri-tumoral stroma (PTS) and cathepsin G was localized to the phenotypic mast cells within the PTS. Western blotting demonstrated protein expression of cathepsin B and D, and RT-qPCR demonstrated transcript expression of all three cathepsins. Enzyme activity assays showed that cathepsin B and D to be active. Conclusion: The presence of cathepsins B and D on the CSCs and cathepsin G on the phenotypic mast cells suggest the presence of bypass loops for the RAS which may be a potential novel therapeutic target for mHNcSCC.